(untitled) (TEST Ticontre. Theory Text Translation, 2016)
In 1983 Giulio Einaudi asked Primo Levi to translate Kafka’s Trial for the new series «Scrittori tradotti da scrittori». The proposal sounded original and provocative, and Levi accepted eagerly. The translation, however, had a negative effect on him. While working on The Trial, Levi relived his Auschwitz season, revived his deepest fears, and fell back into depression: he felt as if he was himself on trial. This was partially due to a clash of literary styles as well as to two contrasting – and yet at times kindred – conceptions of language and communication. The present study addresses the following questions: were Levi and Kafka’s literary styles as opposed as Levi implies? How is Levi’s “obscure part” connected to Kafka? Why did Levi associate The Trial with his Holocaust experience and identify himself with Josef K.? What does Levi’s encounter with Kafka tell us about the shame of being human and our capacity to give an account of ourselves? By investigating Levi’s uncanny encounter with Kafka, my essay will discuss Levi’s theory of language, showing how the Levi-Kafka intersection opens up new ways of interpreting Levi’s concerns about communication, the work of the witness, moral responsibility, and shame, which coalesced into the reflections of The Drowned and the Saved. Nel 1983 Giulio Einaudi chiese a Primo Levi di tradurre Il processo di Kafka per la nuova serie Scrittori tradotti da scrittori. La proposta parse a Levi originale ed intelligente, sicché la accettò immediatamente. La traduzione ebbe tuttavia un effetto negativo su di lui. Mentre lavorava al Processo, Levi rivisse la stagione di Auschwitz, risentì le sue più profonde paure e ricadde in depressione. Si sentiva come se fosse lui stesso processato. Ciò era in parte dovuto a due opposte concezioni di stile letterario e a due divergenti – anche se a volte paradossalmente affini – concezioni del linguaggio e della comunicazione. Il presente contributo si interroga su una serie di domande: gli stili di Levi e Kafka sono così opposti come sembrano? Che legame c’è tra la «parte oscura» di Levi e Kafka? Perché Levi associò Il processo con la sua esperienza ad Auschwitz e si identificò con Josef K.? Che cosa ci rivela l’incontro tra Levi e Kafka della vergogna di essere un uomo e della nostra capacità di «dar conto di noi stessi»? Analizzando il perturbante incontro tra Levi e Kafka, il mio saggio discute la «teoria del linguaggio» di Levi e mostra come l’intersezione tra Levi e Kafka apre nuove prospettive di interpretazione riguardo alle preoccupazioni di Levi per la comunicazione, il ruolo del testimone, la responsabilità morale e la vergogna. Tali temi confluirono nelle riflessioni de I sommersi e i salvati e verranno esaminati nella parte finale del presente saggio. PAROLE CHIAVE Kafka; The Drowned and the Saved; trial; translation; communication; language; obscure; clear; shame; guilt.